2020
DOI: 10.1002/2211-5463.12801
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity pulsed ultrasound inhibits VEGFA expression in chondrocytes and protects against cartilage degeneration in experimental osteoarthritis

Abstract: Low‐intensity pulsed ultrasound (LIPUS), a noninvasive physical therapy, was recently demonstrated to be an effective treatment for osteoarthritis (OA). Vascular endothelium growth factor A (VEGFA) has been found to be upregulated in the articular cartilage, synovium and subchondral bone of OA patients, leading to cartilage degeneration, synovitis and osteophyte formation. However, the functions and mechanisms of LIPUS in regulating chondrocyte‐derived VEGFA expression are still unclear. In this study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The clinical LIPUS therapeutic system (Smith & Nephew Exogen 4000, USA) was performed. The LIPUS parameters were 30 ​mW/cm 2 , 1.5 ​MHz and 20 ​% duty cycle, which were consistent with the previous studies [ 13 , 14 ]. FLS were treated with TGF-β1 (10804, Sino Biological, China) at 10 ​ng/mL for 24 ​h to induce a fibrotic response [ [24] , [25] , [26] ].…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…The clinical LIPUS therapeutic system (Smith & Nephew Exogen 4000, USA) was performed. The LIPUS parameters were 30 ​mW/cm 2 , 1.5 ​MHz and 20 ​% duty cycle, which were consistent with the previous studies [ 13 , 14 ]. FLS were treated with TGF-β1 (10804, Sino Biological, China) at 10 ​ng/mL for 24 ​h to induce a fibrotic response [ [24] , [25] , [26] ].…”
Section: Methodssupporting
confidence: 91%
“…Furthermore, another study found that cartilage-specific ablation of mTOR could significantly reduce synovial fibrosis [ 32 ]. It has further been reported that LIPUS could regulate the function of synovial macrophages and chondrocytes in OA [ 13 , 14 , 33 ], demonstrating that the inhibition of synovial fibrosis by LIPUS may be a comprehensive effect. In OA synovial membranes, synovial macrophages produce tumor necrosis factor and IL-1β to promote the inflammatory and destructive response of FLS, as well as stimulate the proliferation of the synovium [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, other studies demonstrated that FER1L4 promotes VEGFA expression through sequestration of miR-874-3p. VEGFA has been shown to participate in OA 22 , 23 . Targeting VEGF or its receptors to inhibit VEGF signaling showed could be a potential stand-alone or adjuvant therapy for OA 24 .…”
Section: Introductionmentioning
confidence: 99%